REMEDIASI KESALAHAN SISWA MENYELESAIKAN SOAL MENGGUNAKAN ADVANCE ORGANIZER BERBANTUAN LKS DI SMA - Nashrullah, Nashrullah; S, Stepanus Sahala; Arsyid, Syaiful B (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of study is to know that advance organizer learning model helped worksheet can remediate students’ error in solving Kirchoff’s second law problems in SMA Negeri 3 Pontianak. The type of study is pre-experimental design with one-group pretest-posttest design. The sample of this study was selected using intact group technique to obtain 34 students from class X H. Data collection instrument used is four essay questions that have been validated (validity is 3.5 on medium category) and tested for its reliability (reliability is 0.649 on high category). Based on data analysis obtained that the most students’ error on solving Kirchhoff's second law ploblems is calculation error by 77% in pre-test and post-test current 36%. As for the average decrease in students’ error on solving the Kirchoff’s second law after being given remedy using advance organizer learning model by 75% with the effectiveness of 0.756. Thus, advance organizer learning model helped worksheet can remediate the students' error on solving Kirchoff’s second law problem at SMA Negeri 3 Pontianak. So, hopefully the result of study can be used as reference of teacher in learning.Keywords    : Advance organizer, worksheet, students’ error, Kirchoff second law